Perubahan Bentuk Penggunaan Lahan Di Desa Panggreh Akibat Relokasi Korban Bencana Lumpur Lapindo - Hilmi Zain Muafi; Moch. Shofwan (LPPM Universitas Putera Batam, 2023)
The Lapindo mud disaster forced local residents to flee to a safe place, one of which was Panggreh Village, which has an area of ​​171.78 hectares or 3%. As a result, the population in Panggreh Village has automatically increased. Several cases show that if there is a change or regional development in a location, then in a short time the land around it will also change progressively. The purpose of this study was to determine changes in the form of land use in Panggreh Village due to the relocation of victims of the Lapindo Mud Disaster. Collecting data in this study using documentation, observation and using Google Earth imagery. The analytical method used is quantitative descriptive analysis with a before-after analysis technique. The results showed that there was a significant increase and decrease in land use that occurred in Panggreh Village in 2005 and 2022. The residential land area in 2005 was 48.95 Ha and in 2022 it increased to 69.99 Ha or 59%, The area of ​​paddy fields in 2005 was 109.32 Ha and in 2022 it decreased to 94.69 Ha or 46%, The area of ​​dry land or fields in 2005 was 13.51 Ha and in 2022 it decreased to 7.10 Ha or 34 %. Government policies related to land use and population are expected to be realized in the community so that there are no policy deviations that originate from uncontrolled population growth and land use that is not in accordance with the policy.